Chinese medicine targets cellular autophagy against cardiovascular diseases: research progress and future prospects - Chen, Zhengyu; Dou, Jinjin; Zhang, Xiwu (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs) pose a serious threat to human health and represent one of the leading causes of death worldwide. Cellular autophagy, an essential intracellular self-degradation and homeostasis maintenance mechanism, plays a pivotal role in the pathogenesis of cardiovascular diseases. Traditional Chinese Medicine (TCM), with its unique theoretical framework and therapeutic principles, has demonstrated remarkable efficacy in CVDs management, garnering increasing scientific attention. In recent years, growing research attention has focused on TCM's autophagy regulation for CVDs treatment. However, most studies remain limited to cellular and animal models, with insufficient clinical data and unclear specific metabolic pathways and targets. Therefore, it is imperative to (1) investigate autophagy mechanisms in depth (2), explore methods for autophagy balance, and (3) clarify drug interactions to establish a foundation for clinical applications. This article comprehensively summarizes relevant research findings, provides an in-depth discussion of TCM's mechanisms in autophagy regulation for CVDs treatment, reviews current research status, and outlines future development trends, aiming to offer valuable theoretical foundations and therapeutic strategies for clinical CVDs management.